JURIDICAL ANALYSIS OF DECISION NUMBER 457/PID.SUS/2025/PN MDN CONCERNING THE CRIMINAL ACT OF OFFERING FOR SALE, SELLING, AND ACTING AS AN INTERMEDIARY FOR CLASS I NARCOTICS - Sunardi; Bonanda Japatani Siregar (CV. Barokah Publsiher, 2026)
This study aims to juridically analyze the fulfillment of the elements of the criminal offense, to assess the quality of evidence and the application of the evidentiary system under the Indonesian Criminal Procedure Code (KUHAP), and to examine the conformity of the judges’ considerations in sentencing from the perspective of the principle of proportionality and the objectives of punishment. The results of the study indicate that the elements of the criminal offense as formulated in Article 114 paragraph (1) of Law Number 35 of 2009 concerning Narcotics have been fulfilled lawfully and convincingly. The element of “any person,” the element of “without right or against the law,” and the element of “selling Class I narcotics” were proven through facts revealed during the trial, supported by witness testimony, the defendant’s statement, physical evidence, and documentary evidence. The panel of judges applied substantive law appropriately by assessing the elements of the offense based on normative construction and legal facts. Accordingly, the application of Article 114 paragraph (1) of the Narcotics Law in the a quo case is consistent with the prevailing positive law. The quality of evidence and the application of the evidentiary system in Decision Number 457/Pid.Sus/2025/PN Mdn are in accordance with the provisions of the Indonesian Criminal Procedure Code.